Norming of Coloured Progressive Matrices Test in Elementary School Children Based on Classical Measurement Theory and Rasch Modeling - Uly Gusniarti; Mira Aliza Rachmawati; Susilo Wibisono; Libbie Annatagia; Ike Agustina; Rumiani Rumiani (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2021)
This study aimed to develop Coloured Progressive Matrices (CPM) norms for the use in the Indonesian context. We used two approaches, namely classical test theory (CTT) which uses raw score (total score) as measurement result information and Rasch modeling which uses logit value as measurement result information. This research was conducted in four regencies and one municipality in the Province of Yogyakarta. The participants were 1,779 elementary school age children recruited through random sampling. The norming analysis in this study divided the data into five age groups in the range of 6 – 12.5 years old. The level of intelligence represented by the results of the CPM measurement consists of five levels, from Grade I to Grade V. Grade V as the lowest intelligence level has a value below the 5th Percentile of the data distribution. Grade IV as the second lowest level of intelligence was located between between the 5th and 25th Percentile of the data distribution. Grade III representing the average level of intelligence had the greatest range from 25th to 75th Percentile. In addition, the range allocated for Grade II was similar to Grade IV, but in the opposite direction of the distribution (i.e., between 75th and 95th Percentile). Lastly, Grade I as a representation of the highest level of intelligence is in the range of values above the 95th Percentile.